Congruence and discrepancy in Asian American women's perception and stress appraisal of gendered racial microaggressions: Relationships with depressive symptoms and internalized racism - Keum, Brian TaeHyuk; Wong, Michele J. (Frontiers in Public Health, 2022)
Prior research demonstrates significant links between discrimination and mental health by assessing either encounters with or stress appraisal of discrimination. However, research has yet to examine the dynamic interplay between frequency and stress appraisal (e.g., high frequency-low stress appraisal) and their linkage to depressive symptoms. Using a sample of 309 Asian American women (Mage = 22.81, SD = 0.26), we used a polynomial regression and response surface analysis to model the congruence and discrepancy between frequency and stress appraisal of gendered racial microaggressions experienced by Asian American women and how they are related to depressive symptoms and internalized racism. The dynamics between frequency and stress in relation to depressive symptoms were further probed at low, mean, and high levels of internalized racism. Greater congruence between frequency and stress was significantly associated with depressive symptoms (medium to large effect) and internalized racism (small effect). A discrepancy between higher frequency and lower stress was significantly associated with greater internalized racism. Further, when looking across levels of internalized racism, greater congruence between frequency and stress was significantly associated with greater depressive symptoms at low and mean levels of internalized racism but not at high levels. Gendered racial microaggressions are associated with adverse mental health outcomes among Asian American women, contributing to greater depressive symptoms and internalized racism. Further consideration should be given toward how internalized racism shapes differences in the perceptions and stress appraisal of gendered racial microaggressions, and subsequent mental health outcomes among Asian American women.